Contribution of Elevated Glucose and Oxidized LDL to Macrophage Inflammation: A Role for PRAS40/Akt-Dependent Shedding of Soluble CD14 - Lucía Sanjurjo; Esmeralda Castelblanco; Josep Julve; Nuria Villalmanzo; Érica Téllez; Anna Ramirez-Morros; Núria Alonso; Dídac Mauricio; Maria-Rosa Sarrias (MDPI AG, 2023)
Atherosclerosis, a process in which macrophages play a key role, is accelerated in diabetes. Elevated concentrations of serum-oxidized low-density lipoproteins (oxLDL) represent a common feature of both conditions. The main goal of this study was to determine the contribution of oxLDL to the inflammatory response of macrophages exposed to diabetic-mimicking conditions. THP1 cells and peripheral blood monocytes purified from non-diabetic healthy donors were cultured under normal (5 mM) or high glucose (HG) (15 mM) with oxLDL. Then, foam cell formation, expression of CD80, HLADR, CD23, CD206, and CD163, as well as toll-like receptor 4 (TLR4) and co-receptors CD36 and CD14 (both at the cell surface and soluble (sCD14)), and inflammatory mediators' production were measured by flow cytometry, RT-qPCR, or ELISA. Additionally, serum sCD14 was determined in subjects with subclinical atherosclerosis with and without diabetes by ELISA. Our results showed that oxLDL-mediated intracellular lipid accumulation via CD36 increased under HG and that HG + oxLDL enhanced TNF, IL1B, and IL8, and decreased IL10. Moreover, TLR4 was upregulated in macrophages under HG and monocytes of subjects with diabetes and atherosclerosis. Interestingly, HG-oxLDL upregulated CD14 gene expression, although its total cellular protein abundance remained unaltered. sCD14 shedding via PRAS40/Akt-dependent mechanisms, with pro-inflammatory activity, was significantly increased in cultured macrophages and plasma from subjects with diabetes and subclinical atherosclerosis or hypercholesterolemia. Our data support an enhanced synergistic pro-inflammatory effect induced by HG and oxLDL in cultured human macrophages, possibly explained by increased sCD14 shedding.